Extracellular Cardiolipin Modulates Select Immune Functions of Astrocytes in Toll-Like Receptor (TLR) 4-Dependent Manner - Taryn E. Murray; Tyler J. Wenzel; Svetlana Simtchouk; Bridget K. Greuel; Julien Gibon; Andis Klegeris (Mediators of Inflammation)
Alzheimer’s disease (AD) is characterized by chronic neuroinflammation, which is partially mediated by dysregulated functions of glial cells. Cardiolipin (CL) is a phospholipid normally confined to the inner mitochondrial membrane; however, it has been detected in human sera, indicating that it can exist in the extracellular space where it may interact with nearby cells. Although CL has been shown to modulate several functions of microglia in a toll-like receptor (TLR) 4-dependent manner, the effects of extracellular CL on astrocytes are unknown. In addition to their homeostatic functions, astrocytes participate in neuroimmune responses of the brain and express TLR 4. Therefore, we hypothesized that extracellular CL (1) modulates the secretion of cytokines and cytotoxins by astrocytes, as well as their phagocytic activity, and (2) acts by interacting with astrocyte TLR 4. We demonstrate that CL inhibits the lipopolysaccharide- (LPS-) induced secretion of cytotoxins and expression of glial fibrillary acidic protein (GFAP) by human U118 MG astrocytic cells. CL alone upregulates the phagocytic activity of human astrocytic cells and primary murine astrocytes. CL in combination with LPS upregulates secretion of interleukin (IL)-1β by astrocytic cells. Furthermore, CL alone increases the secretion of monocyte chemoattractant protein (MCP)-1 by astrocytic cells, which is blocked by the TLR 4-specific antagonist TAK-242. We demonstrate that CL upregulates MCP-1 secretion in the absence of its natural carrier protein, β2-glycoprotein 1, indicating that CL may be bioactive in the brain where this protein is not present. Lastly, we show that CL downregulates the expression of astrocytic TLR 4, implying that CL engages this receptor, as its activation has been shown to lead to its degradation. Overall, our study extends the list of cell type functions of which CL modulates and provides evidence that CL, or liposomes containing this phospholipid can be used to modulate specific neuroimmune functions of astrocytes.